The model of development and evolution of the spatial structure of Daedeok Innopolis: From science town to innovative ecosystem - Hafez Mahdnejad; Ahmad zanganeh (تحقیقات کاربردی علوم جغرافیایی)
Innopolis Daedeok is a beacon of scientific excellence and technological innovation, serving as the nerve center of South Korea's research endeavors. By leveraging the presence of esteemed research institutions and universities, this hub has created a fertile ground for commercializing cutting-edge technologies. The research methodology employed is descriptive-analytical and developmental in nature. The findings indicate that Innopolis Daedeok is strategically divided into five distinct regions, spanning 27.7 square kilometers, to achieve its operational objectives. Notably, 11% of South Korea's Ph.D.-level researchers are affiliated with Innopolis Daedeok. Currently, a workforce of 22,000 researchers and employees is engaged in advanced research, with 10% of the country's research workforce concentrated in this hub. The spatial expansion of Innopolis Daedeok has unfolded in four stages: the establishment of the Daedeok Science Town (1973-1993), the creation of innovation (1993-1997), the formation of an innovation cluster (1998-2003), and the growth stage of the innovation cluster (2004 to present). This evolution has enabled Innopolis Daedeok to become a global innovation hub, with a unique triple helix model of government, industry, and academia collaboration. The development and evolution model of Innopolis Daedeok is characterized by three distinct stages: the initial stage (science park model), the development stage (technopolis model), and the maturity stage (innovation cluster model). This model serves as a benchmark for other innovation hubs, highlighting the importance of strategic planning, collaboration, and investment in research and development.